Barcoding of live human PBMC for multiplexed mass cytometry() - Mei, Henrik E. (J Immunol, 2015)
Mass cytometry is developing as a means of multiparametric single cell analysis. Here, we present an approach to barcoding separate live human PBMC samples for combined preparation and acquisition on a CyTOF(®) instrument. Using six different anti-CD45 antibody (Ab) conjugates labeled with Pd104, Pd106, Pd108, Pd110, In113, and In115, respectively, we barcoded up to 20 samples with unique combinations of exactly three different CD45 Ab tags. Cell events carrying more than or less than three different tags were excluded from analyses during Boolean data deconvolution, allowing for precise sample assignment and the electronic removal of cell aggregates. Data from barcoded samples matched data from corresponding individually stained and acquired samples, at cell event recoveries similar to individual sample analyses. The approach greatly reduced technical noise and minimizes unwanted cell doublet events in mass cytometry data, and reduces wet work and antibody consumption. It also eliminates sample-to-sample carryover and the requirement of instrument cleaning between samples, thereby effectively reducing overall instrument runtime. Hence, CD45-barcoding facilitates accuracy of mass cytometric immunophenotyping studies, thus supporting biomarker discovery efforts, and should be applicable to fluorescence flow cytometry as well.